A study of adsorption isotherms for the removal of herbicide Atlantis WG from aqueous solutions by using Bentonite clay (Baghdad Science Journal, 2015)
The subject of this research involves studying adsorption to removal herbicide Atlantis WG from aqueous solutions by bentonite clay. The equilibrium concentration have been determined spectra photometry by using UV-Vis spectrophotometer. The experimental equilibrium sorption data were analyzed by two widely, Langmuir and Freundlish isotherm models. The Langmuir model gave a better fit than Freundlich model The adsorption amount of (Atlantis WG) increased when the temperature and pH decreased. The thermodynamic parameters like ?G, ?H, and ?S have been calculated from the effect of temperature on adsorption process, is exothermic. The kinetic of adsorption process was studied depending on Lagergren ,Morris ? Weber and Rauschenberg equations.